'Am I a terrorist or an educator?' Turkish asylum seekers narratives on education rights violations after a crackdown following the 2016 failed coup attempt in Turkey. (1st January 2023) - Aydin, Hasan; Avincan, Köksal
ABSTRACT: Democratisation in Turkey collapsed in the wake of the 2016 failed military coup and the crackdown that followed, with President Recep Tayyip Erdoğan launching a widespread rollback of academic and other liberties, systematically purging civic institutions of political opponents and critics that significantly harmed intellectuals, students, and educational rights. This paper analyses the narratives of Turkish citizens who were prosecuted, dismissed, abused, tortured, victimised, and imprisoned during the State of Emergency (OHAL) initiated after the failed coup attempt in July 2016. This narrative approach examines the transcripts of in-depth interviews about the experiences and critical life stories of 20 individuals now living in the United States, Canada, and Europe. Also included are field notes and documents that reveal the authorities' violations of their educational human rights. These included the denial of education, unwarranted dismissal, elimination of academic freedom of thought, and harassment of academics and their children. Such violations have created a brain drain of educators fleeing the country. These deleterious changes in the Turkish education system have had severe social and political effects and have produced an education system that fails to meet the country's needs, which, if not remediated, will ripple through the generations, dimming the nation's future.